Contesting educational imaginaries at the intersection of migration and transnational development in Guatemala. - Nichols, Briana (Anthropology & Education Quarterly, 2024)
Drawing on 18 months of ethnographic engagement in Guatemala with Indigenous youth, local community organizations, and transnational nongovernmental organizations, this article examines how young people imagine and work toward alternative futures at the intersection of extensive migration and a developmentalist push for educational attainment. I show how, within the development infrastructures generated by migration, contrasting futures are rendered, with concerns over education being a key site for this imaginative and future‐oriented work.